Decoding Emotional Intelligence of Hospitality Workforce in Bali: Generation Z Perspectives - Indrayani, I Gusti Ayu Putu Wita; Sekarti, Ni Ketut; Puspa Adi, Ida Ayu Sri; Arthini, Ni Nyoman Suci; Pitanatri, Made Uttari (Institut Pariwisata Trisakti, 2024)
Emotional intelligence plays a central role in the hospitality industry as it significantly influences service quality, workplace relationships, and hotel reputation. However, empirical studies on emotional intelligence in previous literature have not specifically focused on Generation Z, the youngest generation entering the workforce. This research aims to identify the emotional intelligence of Generation Z employees. The research adopts a sequential explanatory mixed-method approach, utilizing a questionnaire distributed to 115 Generation Z employees and conducting interviews with middle and top managerial levels in five-star hotels in Bali. The research findings indicate that the emotional intelligence of Generation Z employees varies at different levels across various dimensions. While employees demonstrate an understanding of their own emotions and effectively manage them in service delivery, there is a need for improvement in their ability to comprehend the emotions of others. The practical implications of these findings suggest that hotel management should focus on creating a supportive work environment that enhances employee well-being, including adjustments to work schedules, stress management, and well-being programs to maintain their emotional balance. This study may significantly contribute to the development of effective strategies to optimize the potential of Generation Z employees in achieving service excellence and organizational success. Keywords: hospitality, psychological capital, subjective well-being